2008
DOI: 10.1901/jaba.2008.41-273
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Activity Attendance and Engagement in Individuals With Dementia Using Descriptive Prompts

Abstract: The effects of providing descriptive prompts to increase activity attendance and engagement in 6 individuals with dementia were evaluated using a reversal design. The results showed that providing descriptive prompts increased activity attendance and engagement for all participants. The results support the use of antecedent interventions for increasing appropriate behavior by individuals with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 6 publications
1
23
0
Order By: Relevance
“…For instance, antecedent events such as prompts to engage in an activity (Brenske, Rudrud, Schulze, & Rapp, 2008;Engelman, Altus, & Mathews, 1999), activity prompts that include positive social attention (Polenick & Flora, 2011), or the presentation of activity materials in a salient location may momentarily establish the reinforcing effectiveness of activity engagement or social interaction, and may evoke behaviors associated with these events (Michael, 1993). Positive staff engagement has been significantly correlated with levels of interest, pleasure, and participation during activities for older nursing home residents (Meeks & Looney, 2011); thus, the social engagement of caregivers or family members may further increase activity participation and enjoyment.…”
Section: Directions For Future Investigationmentioning
confidence: 99%
“…For instance, antecedent events such as prompts to engage in an activity (Brenske, Rudrud, Schulze, & Rapp, 2008;Engelman, Altus, & Mathews, 1999), activity prompts that include positive social attention (Polenick & Flora, 2011), or the presentation of activity materials in a salient location may momentarily establish the reinforcing effectiveness of activity engagement or social interaction, and may evoke behaviors associated with these events (Michael, 1993). Positive staff engagement has been significantly correlated with levels of interest, pleasure, and participation during activities for older nursing home residents (Meeks & Looney, 2011); thus, the social engagement of caregivers or family members may further increase activity participation and enjoyment.…”
Section: Directions For Future Investigationmentioning
confidence: 99%
“…Dementia is a cluster of behavioral deficits secondary to neurological degeneration and is associated with deterioration in verbal, social, and daily living skills (Maj & Sartorious, 2002). Several studies have demonstrated the success of behavioral interventions in maintaining adaptive skills in elderly individuals; however, many were multicomponent interventions that relied on participants' ability to respond to instructions (e.g., Bourgeois, 1990; Brenske, Rudrud, Schulze, & Rapp, 2008). Direct, differential reinforcement may be required with individuals who no longer respond to instructions.…”
mentioning
confidence: 99%
“…There is evidence for some cognitive, occupational therapy and psychotherapy approaches, for example (Brenske et al 2008;Joosten-Weyn Banningh et al 2008;Angevaren et al 2008), support groups (Snyder et al 2007), relaxation, and memory training (Rapp et al 2002). The limited research suggests that self-management programmes could be beneficial to people with dementia for developing physical and emotional self-management strategies (Mountain 2006).…”
Section: Introductionmentioning
confidence: 99%